High-mobility group box 1-mediated heat shock protein beta 1 expression attenuates mitochondrial dysfunction and apoptosis. (May 2015) - Narumi, Taro; Shishido, Tetsuro; Otaki, Yoichiro; Kadowaki, Shinpei; Honda, Yuki; Funayama, Akira; Honda, Shintaro; Hasegawa, Hiromasa; Kinoshita, Daisuke; Yokoyama, Miyuki; Nishiyama, Satoshi; Takahashi, Hiroki; et al.
Abstract: Aims: Apoptosis of cardiomyocytes is thought to account for doxorubicin cardiotoxicity as it contributes to loss of myocardial tissue and contractile dysfunction. Given that high-mobility group box 1 (HMGB1) is a nuclear DNA-binding protein capable of inhibiting apoptosis, we aimed to clarify the role of HMGB1 in heat shock protein beta 1 (HSPB1) expression during doxorubicin-induced cardiomyopathy. Methods and results: Mitochondrial damage, cardiomyocyte apoptosis, and cardiac dysfunction after doxorubicin administration were significantly attenuated in mice with cardiac-specific overexpression of HMGB1 (HMGB1-Tg) compared with wild type (WT) -mice. HSPB1 levels after doxorubicin administration were significantly higher in HMGB1-Tg mice than in WT mice. Transfection with HMGB1 increased the expression of HSPB1 at both the protein and mRNA levels, and HMGB1 inhibited mitochondrial dysfunction and apoptosis after exposure of cardiomyocytes to doxorubicin. HSPB1 silencing abrogated the inhibitory effect of HMGB1 on cardiomyocyte apoptosis. Doxorubicin increased the binding of HMGB1 to heat shock factor 2 and enhanced heat shock element promoter activity. Moreover, HMGB1 overexpression greatly enhanced heat shock element promoter activity. Silencing of heat shock factor 2 attenuated HMGB1-dependent HSPB1 expression and abrogated the ability of HMGB1 to suppress cleaved caspase-3 accumulation after doxorubicin stimulation. Conclusions: We report the first in vivo and in vitro evidence that cardiac HMGB1 increases HSPB1 expression and attenuates cardiomyocyte apoptosis associated with doxorubicin-induced cardiomyopathy. Cardiac HMGB1 increases HSPB1 expression in cardiomyocytes in a heat shock factor 2-dependent manner. Highlights: HMGB1 overexpression increased HSPB1 levels after doxorubicin administration. HSPB1 expression was regulated by HMGB1 and HSF2 after doxorubicin administration. HMGB1 overexpression attenuated cleaved caspase-3 levels and apoptosis. Mitochondrial dysfunction was suppressed in doxorubicin-treated HMGB1-Tg mice. The survival rate against doxorubicin was higher in HMGB1-Tg mice than in WT mice.